Advanced numerical simulation of hybrid nanofluid radiative flow with Cattaneo-Christov heat flux model over a rotating disk: Innovative iterative techniques - Muhammad Jebran Khan; Samina Zuhra; Zareen A. Khan; Mohsin Ali; Li Chen; Abdul Haq; Firas Zawaideh; Radwan M. Batyha; Diaa Salama AbdElminaam (Case Studies in Thermal Engineering)
This paper investigates the effect of nonlinear thermal radiation on SWCNT-TiO2 and MWCNT-CoFe2O4 nanoparticles suspended in a water-based hybrid nanofluid, flowing past rotating disks. The study employs the Cattaneo-Christov heat flux model to capture the influence of non-Fourier heat conduction. The rotational motion of the disks generates the fluid flow, and the governing partial differential equations are transformed into dimensionless forms using similarity variables. These equations are then solved using a New Iterative Technique (NIT) in Mathematica, which is known for its rapid convergence and accuracy. The analysis focuses on the behavior of various parameters, including velocity components (û, vˆ, ŵ), temperature (Tˆ), and thermal conductivity (kˆ), under different heat transfer conditions. Graphical representations illustrate the effects of these parameters, providing insights into the thermal and fluid dynamic performance of the hybrid nanofluid. The study demonstrates that the NIT is highly effective for solving complex fluid dynamics problems, offering precise and swift solutions. NIM provide an efficient and accurate solution for complex nonlinear problems, overcoming the limitations of traditional methods. This approach enhances computational efficiency and solution accuracy in modeling hybrid nanofluid behavior. This research contributes to the understanding of hybrid nanofluids in engineering applications, particularly in optimizing heat transfer in systems involving rotating machinery.